Determinants of diabetic wound healing in patients at the Cipadu Community Health Center, Tangerang City - Ernawati, Any; Purnamawati, Dewi (Science Midwifery, 2025)
Diabetes mellitus (DM) is a common chronic disease with serious complications including diabetic wounds. DM complications result in chronic wounds that require specialized care and considerable time. The prevalence of diabetic wounds continues to increase globally, including in Indonesia, where this complication accounts for the majority of lower limb amputation cases. To know the determinants of wound care on the healing of diabetes in patients at Cipadu Community Health Center. This study uses a cross-sectional study design by collecting medical record data from DM patients who underwent treatment or care at Cipadu Community Health Center from January 2022 to December 2022. There are 65 patients in the study population who met the inclusion and exclusion criteria. The data were analyzed descriptively using statistical methods such as the chi-square test and logistic regression to identify relationships between variables. The study results show that a regular wound care schedule and a combination of modern traditional wound care have significant effectiveness in the healing process of diabetic ulcers. Multivariate analysis revealed that wound care is the healing of diabetic wounds while the wound care schedule is a control variable. Factors such as age, gender, and wound stage did not show a significant relationship with wound healing.